DETERMINANTS OF GOING CONCERN AUDIT OPINIONS IN REAL ESTATE AND PROPERTY COMPANIES LISTED ON THE IDX - Jenny Zain; Bunga Hanggraini Meiviandra; Trica Angkat; Widodo Sinaga; Oky Syahputra (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine the effect of Audit Quality, Company Size, KAP Reputation and Audit Tenure on Going Concern Audit Opinions. This research is focused on Real Estate and Property companies listed on the IDX in 2020-2022 with a total of 81 samples. The data analysis technique used is using SPSS software with the aim of obtaining accurate calculation results and facilitating proper data processing. The results of this study are audit quality, KAP reputation, and audit tenure have no effect on going concern audit opinion. Meanwhile, company size has a significant effect on going concern audit opinion.